2011
DOI: 10.1016/j.rgg.2011.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The Late Paleozoic fold-thrust structure of the Tunka bald mountains, East Sayan (southern framing of the Siberian Platform)

Abstract: According to the new geological, geochronological, and structural data, the Tunka bald mountains (East Sayan) have a nappe structure, which formed in the Late Carboniferous–Early Permian. The deformations have been dated by the 40Ar–39Ar method on the basis of syntectonic micas and amphiboles, whose structural and spatial positions have been determined in oriented thin sections. The geometrical analysis of macro- and microstructures has revealed three development stages of the structures, which followed one an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The epicenters of the studied earthquakes were recorded in the southwest of the Baikal Rift Zone (BRZ) at the southeastern tip of the Main Sayan Fault. This is the largest discontinuous structure with a length of more than 1000 km and a width of about 10 km [7]. This fault retains high geodynamic activity and is included in the East Sayan earthquake source zone.…”
Section: The Baikal Earthquakes For the Period 2020-2021mentioning
confidence: 96%
“…The epicenters of the studied earthquakes were recorded in the southwest of the Baikal Rift Zone (BRZ) at the southeastern tip of the Main Sayan Fault. This is the largest discontinuous structure with a length of more than 1000 km and a width of about 10 km [7]. This fault retains high geodynamic activity and is included in the East Sayan earthquake source zone.…”
Section: The Baikal Earthquakes For the Period 2020-2021mentioning
confidence: 96%
“…1b) (e.g., Zorin 1999; Ruzhentsev et al 2006Ruzhentsev et al , 2007Ruzhentsev et al , 2012Buslov et al 2009;Ryabinin et al 2011;Zhimulev et al 2011). Buslov et al (2009) andZhimulev et al (2011) reported that the Neoproterozoic-Cambrian formations overthrust upon the Middle Ordovician Tunka granite and the Late Devonian-Early Carboniferous Sagan-Sair Formation with an E-W trending plane and dipping less than 30° southward in the Tunka area (L.4; Fig.…”
Section: Distribution Of the Low-angle Southward-dipping Thrust And Rmentioning
confidence: 99%
“…The molasses-like Late Devonian-Early Carboniferous Sagan-Sair Formation overlaps the Tunka granite and Ordovician-Silurian sedimentary rocks (Buslov et al 2009;Zhimulev et al 2011). The rocks of the Tunka terrane form a complex N-verging fold-thrust structure (e.g., Ryabinin et al 2011;Zhimulev et al 2011).…”
Section: Geologymentioning
confidence: 99%
See 2 more Smart Citations